Nano-microcapsules for encapsulating chemical sunscreens and methods of making and using the same
Patent Information
- Application Number
- CN202611521567.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-29
- Publication Date
- 2026-10-30
AI Technical Summary
单纯依靠复配助剂、光稳定剂,难以从根源上克服传统防晒剂多重耐受性不足的固有缺陷
[0020]本发明具有以下有益效果:本发明提供了一种隔离型乙基纤维素/化学防晒剂纳米微胶囊制备技术,通过超分子自组装技术,将复配化学防晒剂包裹于乙基纤维素璧壳之中,制备为平均直径为200nm左右的球形微胶囊。
Smart Images

Figure CN122997973A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of new cosmetic materials, specifically relating to nanocapsules for encapsulating chemical sunscreens, their preparation methods, and applications. Background Technology
[0002] Sunscreen cosmetics are an important category in the cosmetics industry. Sunscreen agents, as the core raw materials for sunscreen cosmetics to exert their protective effect, directly determine the protective ability, skin feel, and storage stability of sunscreen products. Currently, the sunscreen agents used in the industry are mainly divided into two categories: inorganic mineral physical sunscreens and organic chemical sunscreens. Among them, organic chemical sunscreens are widely used in the market due to their outstanding advantages such as light texture, refreshing feel on the skin, and less tendency to leave a white cast. However, existing mainstream chemical sunscreens still have many undeniable shortcomings. Some components have the risk of transdermal absorption, which can easily irritate the skin and even induce contact allergic reactions. At the same time, these raw materials do not disperse well in the formulation system, often requiring the formulation of large amounts of solubilizers and dispersants, increasing the difficulty of formulation development and posing potential risks to the storage stability of the formulation. Furthermore, most chemical sunscreens have limited photostability and are prone to molecular decomposition after exposure to sunlight, causing a decrease and loss of sun protection effectiveness.
[0003] Besides photodegradation caused by sunlight, existing chemical sunscreens generally have weak tolerance to complex formulations and processing environments, which is a key technical obstacle restricting the development of high-performance sunscreen products. Cosmetic manufacturing involves processes such as heating and homogenization shearing, resulting in the coexistence of pH fluctuations, electrolyte ions, and various types of surfactants within the finished product formulation. Traditional chemical sunscreens are prone to hydrolysis and molecular isomerization under high temperatures; changes in pH can alter the dissociation state of sunscreen molecules, leading to precipitation and sedimentation; electrolyte ions within the system can disrupt the original solubility balance, causing the sunscreen components to precipitate and become inactive; interactions with surfactants during formulation can weaken the dissolution and dispersion of sunscreens; and the high-intensity mechanical shearing during production can damage the molecular structure or original dispersion system of sunscreens, further reducing the final sun protection efficacy. The combination of these multiple factors leads to a decrease in product yield and a reduction in shelf-life protective efficacy, significantly increasing the difficulty of formulation adjustment and large-scale production.
[0004] As consumers' skincare awareness improves, the market demands a comprehensive approach to sunscreen products, balancing high-efficiency protection, gentle and low-irritation properties, and processing and storage stability. Simply relying on compounded additives and light stabilizers is insufficient to fundamentally overcome the inherent shortcomings of traditional sunscreens, such as inadequate tolerance.
[0005] Therefore, developing a sunscreen cosmetic that is highly resistant to high temperatures, acid and alkali environments, system ions, surfactants, and mechanical shearing, while also possessing skin-friendly properties, can effectively alleviate multiple technical pain points in the production, processing, formulation, storage, and use of existing raw materials. It can also reduce the dependence of the formulation on auxiliary agents, reduce the risk of skin irritation from raw materials, and ensure the stable output of sunscreen efficacy under complex conditions. This is of great practical significance for promoting the technological iteration of sunscreen cosmetics and meeting the market's real demand for safe and stable sunscreen products. Summary of the Invention
[0006] The purpose of this invention is to provide a nanocapsule for encapsulating chemical sunscreens, its preparation method, and its application.
[0007] To achieve the above-mentioned objectives, the technical solution adopted by the present invention is: a chemical sunscreen microcapsule, wherein the chemical sunscreen microcapsule comprises nanocapsules, the nanocapsule components include a wall material, a solvent, a surfactant in an alcohol phase, and an aqueous phase; the nanocapsule contains a core material, wherein the core material is a chemical sunscreen agent;
[0008] The wall material is ethyl cellulose, and the viscosity grade of the ethyl cellulose is in the range of N3 to N200; the solvent includes ethanol and ethyl acetate, and the content of ethyl acetate in the solvent is ≤20%, v / v; the surfactant includes both lipophilic and hydrophilic surfactants, and the surfactant in the alcohol phase is a mixture of any two of sorbitan oleate, PEG-40 hydrogenated castor oil, or sodium lauryl sulfate; the aqueous phase is an aqueous solution of acetic acid containing sodium lauryl sulfate, and the content of sodium lauryl sulfate (i.e., the surfactant in the aqueous phase) in the aqueous phase is 0.2% to 5.0%, preferably 1%, w / w.
[0009] By mass ratio, the ratio of wall material to core material is 20:1 to 1:3, preferably 1:1;
[0010] By mass ratio, the ratio of wall material to solvent is 1:8 to 1:400, preferably 1:50;
[0011] By mass ratio, the ratio of wall material to surfactant in the alcohol phase is 1:0.25 to 1:1.6, preferably 1:0.4;
[0012] Based on the solvent volume, the ratio of aqueous phase to solvent is 1:4 to 100:1, preferably 1:1, v / v.
[0013] Accordingly, the preparation method of the chemical sunscreen microcapsules includes the following steps:
[0014] (1) Preparation of phase A: Weigh the wall material and core material, add the surfactant, then add solvent, dissolve fully until homogeneous, and adjust the pH to 3.0-5.5 using acetic acid;
[0015] (2) Prepare phase B: Prepare an aqueous solution of acetic acid containing sodium lauryl sulfate, and adjust the pH to 3.0-5.5 using acetic acid;
[0016] (3) Mix phase A and phase B at a flow rate of 7:3 to 1:20 in a stator-rotor homogenizer or ultrasonic emulsifier to achieve self-assembly and encapsulation of the supramolecular nanocapsules.
[0017] (4) Wall-shell solidification: The nanocapsules prepared in step (3) are chemically cross-linked with glutaraldehyde to obtain solidified microcapsules;
[0018] (5) Separate the solidified microcapsules from the system.
[0019] Accordingly, the preparation method is applied in the preparation of sunscreen cosmetics. The sunscreen cosmetics include the chemical sunscreen microcapsules, and may also contain cosmetically acceptable excipients, such as emollients (e.g., moisturizing oils), humectants, preservatives, sensory modifiers (e.g., fragrances, skin feel modifiers), antioxidants, etc., depending on the product formulation and actual needs.
[0020] The present invention has the following beneficial effects: The present invention provides a preparation technology for isolated ethyl cellulose / chemical sunscreen nanocapsules. Through supramolecular self-assembly technology, the compounded chemical sunscreen is encapsulated in the ethyl cellulose shell to prepare spherical microcapsules with an average diameter of about 200 nm.
[0021] Under the specific system and reaction conditions provided by this invention, the core material sunscreen agent and the wall material ethyl cellulose can spontaneously complete the core-shell structure construction of the ethyl cellulose shell and the sunscreen agent core through the synergistic effect of hydrophobic effect, directional hydrogen bonding and steric hindrance repulsion. Within the three-dimensional confined space at the hundred-nanometer scale, the core material molecules further undergo secondary self-assembly, spontaneously evolving into a thermodynamically stable liquid crystal state or a spatially oriented microcrystalline state.
[0022] The reaction condition window provided by this invention is relatively narrow. If the reaction conditions and parameters are adjusted beyond a specific range (including the ratio of solvent and aqueous phase, the concentration of surfactant, pH and temperature, etc.), the self-assembly system will collapse as a whole, and the self-assembly of microcapsules cannot be achieved. Only flocculent precipitation can be obtained, and it cannot be encapsulated into spherical particles.
[0023] The chemical sunscreen nanocapsules prepared by this invention achieve effective isolation between the chemical sunscreen and the skin while retaining the light and soft texture of the chemical sunscreen. This significantly reduces the transdermal absorption and adverse reactions such as allergies and irritation of the sunscreen. At the same time, the UV shielding efficiency of the formulation is improved through Mie scattering, which greatly improves the uniform dispersion ability of oil-soluble chemical sunscreen in an aqueous environment. Furthermore, it achieves high tolerance to high temperature, acids and alkalis, ions, surfactants, and mechanical shear.
[0024] This invention is carried out entirely under normal temperature and pressure and mild reaction conditions, resulting in low production costs and easy mass production. It provides an important raw material foundation for the development of high-shield, skin-friendly sunscreen cosmetics. Attached Figure Description
[0025] Figure 1 An optical microscope (1000×) image of the microcapsules prepared for an embodiment of the present invention;
[0026] Figure 2 Scanning electron microscope images of the microcapsules prepared in the embodiments of the present invention;
[0027] Figure 3 The image shows the nanoparticle size analyzer results of the microcapsules prepared in the embodiments of the present invention.
[0028] Figure 4 The microcapsules prepared according to the embodiments of the present invention are examined under a polarizing microscope.
[0029] Figure 5 The graph shows the surface zeta potential analysis results of the microcapsules prepared in this embodiment of the invention after being dispersed in pure water;
[0030] Figure 6 Photograph of the finished microcapsule suspension formulation after standing at room temperature for 1 week;
[0031] Figure 7 A comparison of the effects of homogenous shearing at different rotation speeds over 20 minutes on the stability of microcapsule structures;
[0032] Figure 8 This is a comparison diagram showing the effect of different pH values on the stability of the microcapsule structure; A through E represent pH values of 3.0, 4.0, 9.0, 10.0, and 11.0, respectively.
[0033] Figure 9 The diagram shows the effect of different temperatures on the stability of the microcapsule structure; A is the microscopic examination result after treatment at 70℃, and B is the microscopic examination result after treatment at 80℃.
[0034] Figure 10 The diagram shows the effect of different concentrations of ethanol treatment on the stability of microcapsule structures after 20 minutes; A to D are the microscopic examination results after treatment with 50%, 60%, 70%, and 80% concentrations of ethanol, respectively.
[0035] Figure 11 The diagram shows the effect of different concentrations of surfactant SDS treatment on the stability of microcapsule structures; A and B are the microscopic examination results after treatment with 2% and 5% SDS, respectively.
[0036] Figure 12 The diagram shows the effect of sodium chloride on the structural stability of microcapsules. A shows the microscopic examination results of microcapsules after treatment with 10% sodium chloride (the microcapsules shrink into a raisin shape due to osmotic pressure), and B shows the microscopic examination results of microcapsules that recover their spherical shape in pure water after treatment with sodium chloride.
[0037] Figure 13 A comparison chart of absorbance values for different sunscreen agents;
[0038] Figure 14 The ultraviolet and blue-violet light absorption spectra of the microcapsule suspension formulation and the non-encapsulated control group;
[0039] Figure 15 Microscopic examination results of the product prepared for control example 1 (×600).
[0040] Figure 16 One of the microscopic examination results of the product prepared for control example 2 (×600).
[0041] Figure 17 Figure 2 (×600) shows the microscopic examination results of the product prepared for control example 2.
[0042] Figure 18 Photograph of the product prepared in Control Example 2 after standing for 48 hours;
[0043] Figure 19 Photograph of the product prepared for Comparative Example 3;
[0044] Figure 20 Microscopic examination results of the product prepared for control example 3 (×600).
[0045] Figure 21 Microscopic examination results of the product prepared for control example 4 (×600).
[0046] Figure 22 Microscopic examination results of the product prepared for control example 5 (×600).
[0047] Figure 23 Photograph of the product prepared in Control Example 5 after standing for 48 hours;
[0048] Figure 24 Photograph of the product prepared for Comparative Example 6;
[0049] Figure 25Microscopic examination results of the product prepared for control example 6 (×600).
[0050] Figure 26 Photograph of the product prepared for control example 7;
[0051] Figure 27 Microscopic examination results of the product prepared for control example 7 (×600). Detailed Implementation
[0052] This invention provides a nanocapsule that can be used to encapsulate a chemical sunscreen agent. The nanocapsule components include a wall material, a solvent, a surfactant, and an aqueous phase. The nanocapsule contains a core material, namely a chemical sunscreen agent.
[0053] The wall material is pharmaceutical-grade ethyl cellulose with a viscosity range of N3 to N200, preferably N10 to N100. The surfactant can be any two of sorbitan oleate, PEG-40 hydrogenated castor oil, or sodium lauryl sulfate. Both lipophilic and hydrophilic surfactants are required, with a mass ratio of lipophilic surfactant to hydrophilic surfactant of 5:1 to 1:5, preferably 1:1. The solvent is ethanol and ethyl acetate; ethanol is the main solvent, and ethyl acetate is the co-solvent. The content of ethyl acetate in the solvent is not higher than 20% (v / v), preferably 2% to 10% (v / v). The core material is a chemical sunscreen agent (preferably containing a sunscreen stabilizer and a cosolvent), and may be one or a mixture of several of the following: octocrylene, ethylhexyl salicylate, bis-ethylhexyloxyphenol methoxyphenyl triazine, diethylaminohydroxybenzoyl hexyl benzoate, butyl methoxydibenzoylmethane, ethylhexyl triazine ketone, diethylhexylbutamidotriazine ketone, and ethylhexyl methoxycinnamate. The wall material, core material, solvent, and surfactant together constitute the alcohol phase.
[0054] The aqueous phase is an aqueous solution of acetic acid containing sodium lauryl sulfate (the content of sodium lauryl sulfate in the aqueous phase is 0.2-5.0%, preferably 0.5%-2.0%, w / w) (acetic acid concentration <0.1%, used to adjust pH).
[0055] Preferably, the wall material to core material ratio is 20:1 to 1:3 by mass; the wall material to solvent ratio is 1:8 to 1:400 by mass; the wall material to surfactant in the alcohol phase ratio is 1:0.25 to 1:1.6 by mass; and the aqueous phase to solvent ratio is 1:4 to 100:1, v / v, based on the solvent volume.
[0056] The present invention also provides a method for preparing the aforementioned nanocapsules, which specifically includes the following steps:
[0057] 1. Prepare phase A (alcohol phase): Weigh the wall material and core material, add the surfactant, then add solvent, and dissolve fully until homogeneous. Adjust the pH to 3.0-5.5, preferably 4.0-5.0, using acetic acid.
[0058] 2. Prepare phase B (aqueous phase): Prepare an aqueous solution of acetic acid containing sodium lauryl sulfate, and adjust the pH to 3.0-5.5, preferably 4.0-5.0, using acetic acid;
[0059] Ideally, the pH of the alcohol phase and the aqueous phase should be adjusted to be the same.
[0060] 3. Mix phase A and phase B at a flow rate of 7:3 to 1:20 (preferably 1:1) in a stator-rotor homogenizer or ultrasonic emulsifier (the mixing ratio is the flow rate ratio) to achieve self-assembly, encapsulation, and shaping of the nanocapsule supramolecular structure.
[0061] 4. Wall Shell Curing: The wall shell structure is cured through glutaraldehyde chemical cross-linking, enhancing its physical strength and chemical resistance. The chemical cross-linking method includes: after the encapsulation and shaping in step 3, glutaraldehyde is slowly poured in under continuous low-speed stirring (the lower limit of the speed ensures no sedimentation and aggregation, and the upper limit does not exceed high-strength shear damage, 50-1500 rpm), pH 3.0-7.0, preferably 4.0-5.5, and the mass of glutaraldehyde added is 0.2-1.0 times the amount of wall material used.
[0062] 5. The solidified microcapsules are separated from the system using methods such as centrifugation, membrane separation, and salting-out precipitation. After multiple rounds of washing, an aqueous dispersion suspension is finally prepared. Solid-liquid separation is a conventional technique in this field: centrifugal solid-liquid separation involves high-speed centrifugation followed by resuspending and washing in pure water, with multiple cycles until clean; membrane equipment washing involves filtering out the liquid and then replenishing the filtration with pure water until clean; the cleanliness is indicated by the conductivity of the clarified liquid; the aqueous dispersion involves dispersing the high-concentration microcapsule slurry in an aqueous solution, achieving uniform dispersion through low-speed homogenization or continuous stirring.
[0063] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art, and the data obtained are all average values obtained after at least three repetitions, and each repetition yields valid data.
[0064] Example 1: Preparation and Effect Demonstration of Nanocapsules under One Embodiment
[0065] 1. Preparation
[0066] Weigh out 1 kg of each of the following ingredients in a mass ratio of 4:4:3.5:5:1:4:3.5:5, mix them thoroughly, and use them as the core material.
[0067] Following a core-to-wall material mass ratio of 1:1, 1 kg of N10 ethyl cellulose was measured and mixed evenly with the core material. Then, 200 g of sorbitan oleate (surfactant) and 200 g of PEG-40 hydrogenated castor oil (surfactant) were added. Subsequently, 2 L of ethyl acetate was added to fully wet the mixture, followed by 98 L of anhydrous ethanol to fully dissolve the homogeneous phase. The pH was then adjusted to 4.5 using anhydrous acetic acid to obtain phase A (alcohol phase).
[0068] Weigh 1 kg of sodium lauryl sulfate, dissolve it in 100 L of pure water, and adjust the pH to 4.5 with anhydrous acetic acid to obtain phase B (aqueous phase).
[0069] Using the rotor head of a homogenizer as the mixing center or an ultrasonic emulsifying vessel as the mixing center (in this embodiment, the ultrasonic emulsifying vessel is used as the mixing center), phase A and phase B are injected into the mixing center at a flow rate ratio of 1:1. After the two phases are mixed at high speed (25°C, ultrasonic frequency 45KHz), the core material sunscreen agent and the wall material ethyl cellulose spontaneously complete the core-shell structure construction of the ethyl cellulose shell and the sunscreen agent core under the synergistic effect of hydrophobic effect, directional hydrogen bonding and steric hindrance repulsion, forming a milky white and bluish microcapsule suspension.
[0070] Add 0.5 L of 50% (v / v) glutaraldehyde aqueous solution to the microcapsule suspension, crosslink at 40°C for 8 hours to complete the curing of the microcapsule structure, and obtain the cured mixture.
[0071] The solidified mixture was subjected to solid-liquid separation using a 50nm pore size cross-flow filtration membrane system. The filtrate was collected for ethanol recovery and wastewater treatment. After multiple rounds of washing with pure water, the microcapsules were obtained. The microcapsules could be dispersed in an aqueous dispersant as needed to obtain the finished microcapsule suspension. The aqueous dispersant contained pH buffers, surfactants, etc., which are conventional techniques in the field. In this embodiment, the aqueous dispersant used was an aqueous solution containing 0.6% (v / v) 1,2-hexanediol, 0.6% (v / v) p-hydroxyacetophenone, and 2.8% 1,3-butanediol, with a pH of 6.0.
[0072] 2. Basic characteristics
[0073] An optical microscope (1000×) photograph of the microcapsule is shown below. Figure 1 As shown, the scanning electron microscope image is as follows: Figure 2 As shown, the nanoparticle size analyzer analysis results are as follows: Figure 3As shown in the figure. The results show that the microcapsules prepared in this embodiment have an encapsulation rate of more than 98% for the core material, and the finished microcapsules are microspheres with an average particle size of about 200 nm, a polydispersity index (PDI) of about 0.13, and good uniformity.
[0074] Microcapsule microscopic examination results under polarized light microscope are as follows Figure 4 As shown in the figure. The results show that the ordered molecular self-assembly structure of the sunscreen core material inside the microcapsule brings about a significant Maltese cross extinction spot effect, indicating that the microcapsules prepared in this embodiment have achieved supramolecular self-assembly, which is different from the amorphous state of the contents of conventional microcapsule preparation processes.
[0075] After dispersing the microcapsules in pure water, the surface zeta potential was analyzed as follows: Figure 5 As shown, the zeta potential is approximately -40 mV. The finished microcapsule suspension was allowed to stand at room temperature for one week, as... Figure 6 As shown, there was no significant sedimentation, and the dispersion was good.
[0076] 3. Shear resistance, pH, temperature, ethanol, ethylene glycol, surfactant, and sodium chloride tolerance tests were conducted on the microcapsule suspension formulation:
[0077] (1) Shear tolerance test: A stator-rotor homogenizer (rotor diameter 17 mm, stator-rotor spacing 0.5 mm) was used to apply different rotation speeds to the microcapsule suspension at 25℃ for 20 min continuously. The macroscopic physical state and microscopic morphological characteristics of the formulation were examined immediately after shearing and after standing at room temperature for 48 h. The original sample without homogenization and shearing was used as a blank control. At the macroscopic level, the focus was on layering, precipitation and flocculation. At the microscopic level, the integrity of the capsule wall, the uniformity of dispersion and the precipitation of contents were examined. If there were no significant differences between the test sample and the control group in any of the above two time points, the shear condition was deemed to be tolerated. Conversely, if there were significant differences such as phase separation, capsule wall rupture and collapse or precipitation of contents, the formulation was deemed not tolerable. Thus, the upper limit of the critical safe shear speed for maintaining the stability of the formulation was determined.
[0078] (2) pH tolerance test: The microcapsule suspension was adjusted to the target pH value using 5 mol / L sodium hydroxide or hydrochloric acid solution, incubated at 25°C for 20 min, and then returned to the initial pH. The macroscopic physical state (layering, precipitation, and flocculation) and microscopic morphological characteristics (capsule wall integrity, dispersion uniformity, and content precipitation) of the formulation were examined immediately after the pH adjustment and after standing at room temperature for 48 h. The original suspension without pH treatment was used as a blank control. If there were no significant differences between the test sample and the control group in any of the above two time points, the pH condition was determined to be tolerant; otherwise, if there were significant phase separation, capsule wall rupture and collapse, or a large amount of free content, the condition was determined to be intolerant. Based on this, the pH tolerance range for maintaining a stable microcapsule suspension was determined.
[0079] (3) Heat tolerance test: The microcapsule suspension was heated to the target temperature in a water bath and incubated at a constant temperature for 20 min, and then naturally cooled to room temperature. The macroscopic physical state (layering, precipitation and flocculation) and microscopic morphological characteristics (capsule wall integrity, dispersion uniformity and content precipitation) of the formulation were examined immediately after cooling and after standing at room temperature for 48 h. The original suspension without heat treatment was used as a blank control. If there were no significant differences between the test sample and the control group in all indicators at the above two time points, the temperature condition was deemed to be tolerated; otherwise, if there were significant phase separation, capsule wall rupture and collapse or a large amount of free content, the condition was deemed not tolerable. Based on this, the upper limit of the critical safe temperature for the microcapsule suspension to maintain stability and the tolerance temperature range were determined.
[0080] (4) Organic solvent tolerance test: Anhydrous ethanol was added to the microcapsule suspension to the preset target concentration, and the mixture was incubated at room temperature for 20 min and then allowed to return to room temperature equilibrium (if the incubation temperature was not room temperature, cooling was required). The macroscopic physical state (layering, precipitation, and flocculation) and microscopic morphological characteristics (capsule wall integrity, dispersion uniformity, and content precipitation) of the formulation were examined immediately after treatment and after standing at room temperature for 48 h. A suspension diluted with an equal volume of purified water but without ethanol was used as a blank control. If there were no significant differences between the test sample and the control group in any of the above two time points, the ethanol concentration condition was deemed to be tolerated; otherwise, if significant phase separation, capsule wall rupture and collapse, or a large amount of free content appeared, the mixture was deemed to be intolerant. Based on this, the upper limit of the tolerance concentration of the microcapsule suspension to organic solvents was determined.
[0081] (5) Surfactant tolerance test: Sodium dodecyl sulfate was added to the microcapsule suspension to the preset target concentration and incubated at room temperature for 20 min. The macroscopic physical state (layering, precipitation and flocculation) and microscopic morphological characteristics (capsule wall integrity, dispersion uniformity and content precipitation) of the formulation were examined immediately after treatment and after standing at room temperature for 48 h. A suspension with an equal volume of purified water but without surfactant was used as a blank control. If there were no significant differences between the test sample and the control group in any of the above two time points, the concentration condition was deemed to be tolerated; otherwise, if there were significant phase separation, capsule wall rupture and collapse or a large amount of free content, the condition was deemed not tolerable. Based on this, the upper limit of the tolerance concentration of sodium dodecyl sulfate to the microcapsule suspension was determined.
[0082] (6) Ion strength tolerance test: Sodium chloride was added to the microcapsule suspension to the preset target concentration. After incubation at room temperature for 20 min, purified water was added to dilute the sodium chloride content to less than 2% (w / v). The macroscopic physical state (layering, precipitation and flocculation) and microscopic morphological characteristics (capsule wall integrity, dispersion uniformity and content precipitation) of the formulation were examined immediately after dilution and after standing at room temperature for 48 h. The suspension without sodium chloride but diluted in the same way was used as a blank control. If there were no significant differences between the test sample and the control group in any of the above two time points, the ion strength condition was judged to be tolerant; otherwise, if there were obvious phase separation, capsule wall rupture and collapse or a large amount of free content, it was judged to be intolerant. The upper limit of the tolerance of the microcapsule suspension to ion strength was determined accordingly.
[0083] The results are as follows: Figures 7-12 As shown in the figure. The results show that the microcapsule suspension formulation can withstand the shearing of a 7000rpm stator-rotor homogenizer for 20 minutes; the pH tolerance range is 4.0–9.0; after high-temperature treatment at 70℃, the microcapsules remain intact with no core material leakage; it can withstand 10% ethanol or 4% glycol preservative systems; it is highly resistant to nonionic surfactants and also has high tolerance to anionic surfactants; and it can withstand the equivalent ionic strength of 10% sodium chloride.
[0084] 3. Sunscreen efficacy and safety test
[0085] (1) Sun protection effect
[0086] Chemical sunscreen ingredients A and B were selected as control groups. A and B are commercially available sunscreen microcapsule formulations. According to cosmetic ingredient registration information, A contains 30% octocrylene and 9% butyl methoxydibenzoylmethane; B contains 37% ethylhexyl methoxycinnamate. Both microcapsule wall materials are made of silica.
[0087] Group A (encapsulated): Measure 1g of A and disperse it in pure water to a final volume of 1L. Group A (unencapsulated control): Measure 0.3g of octocrylene and 0.09g of butyl methoxydibenzoylmethane, dissolve them in anhydrous ethanol, and bring the volume to 1L. Group B (encapsulated): Measure 1g of B and disperse it in pure water to a final volume of 1L. Group B (unencapsulated control): Measure 0.37g of ethylhexyl methoxycinnamate, dissolve it in anhydrous ethanol, and bring the volume to 1L.
[0088] The microcapsule group prepared by this invention: A formulation containing 1g of microcapsules (dry basis) was weighed and dispersed in pure water to a final volume of 1L. The encapsulated control group prepared by this invention: Bis-ethylhexyloxyphenol methoxyphenyl triazine, butyl methoxydibenzoylmethane, ethylhexyl triazine ketone, and diethylhexylbutamidotriazine ketone, totaling 0.5g, were weighed in a mass ratio of 4:4:3.5:5, dissolved in anhydrous ethanol, and then diluted to a final volume of 1L.
[0089] Take 20 μL of each group of solution (suspension) and place them into flat-bottomed 96-well plates. After complete drying in the dark with forced air, place them in a Thermo Varioskan LUX full-wavelength multifunctional microplate analyzer to measure the absorbance at different wavelengths and calculate the absorbance enhancement ratio: Absorbance enhancement ratio = (Absorbance value of encapsulated group / Absorbance value of unencapsulated control group) - 1. The results are shown in Table 1 and... Figure 13 As shown.
[0090] Table 1 Comparison of absorbance values of different sunscreen agents
[0091]
[0092] The results showed that compared with chemical sunscreens with the same components and different preparation methods, the microcapsule suspension preparation prepared in this embodiment improved the overall UV shielding performance by more than 40%, and the UV shielding performance in the UVA band by more than 140%.
[0093] (2) Safety
[0094] A 24-hour patch test was conducted on the finished microcapsule suspension formulation on human subjects. The method was as follows: 31 subjects aged 18-60 years who met the requirements of Chapter 7, "Human Safety Testing Methods," "2. Human Skin Patch Test," of the *Cosmetic Safety Technical Specifications (2015 Edition)* were selected. No cosmetics, skincare products, beauty devices, or any topical medications were used on the test site within one day prior to the test. The flexor surface of the subject's forearm was used as the test site, which was kept dry and protected from contact with other topical preparations. A 0.5 mm² area was selected. 2 A qualified spot test apparatus with a depth of approximately 1 mm is required. Place 0.025 mL of the finished microcapsule suspension into the spot test apparatus; leave the control well empty. Apply the spot test apparatus containing the test substance to the flexor side of the subject's forearm using hypoallergenic adhesive tape, gently pressing with the palm to ensure even adhesion to the skin, for 24 hours. Observe skin reactions according to the standards in Table 2 at 30 minutes (after the indentation disappears), 24 hours, and 48 hours after removing the spot test apparatus, and record the results.
[0095] Table 2. Criteria for Evaluating Skin Reactions in Repeatable Open Skin Application Tests
[0096]
[0097] The experimental results showed that all subjects had negative reactions. This indicates that the finished microcapsule suspension formulation did not produce significant adverse effects on the experimental subjects, demonstrating high safety.
[0098] 4. Demonstration of the effect of improved UV tolerance
[0099] Measure out a microcapsule suspension containing 1g of microcapsules (dry basis) and disperse it in pure water to a final volume of 1L. Simultaneously, set up a non-encapsulated control group: weigh out 0.5g each of bis-ethylhexyloxyphenol methoxyphenyl triazine, butyl methoxydibenzoylmethane, ethylhexyl triazine ketone, and diethylhexylbutamidotriazine ketone in a mass ratio of 4:4:3.5:5, dissolve them in anhydrous ethanol, and then dilute to a final volume of 1L.
[0100] Take 20 μL of each group of solutions (suspensions) and place them into flat-bottomed 96-well plates. After complete drying in the dark with a forced-air drying fan, place the plates in a xenon lamp solar simulator with an ultraviolet irradiation intensity of 60 W / m². Every 2 hours, place the plates into a Thermo Varioskan LUX full-wavelength multifunctional microplate detector to measure the absorption spectra in the ultraviolet and blue-violet bands. The measurement results are as follows: Figure 14 As shown ( Figure 14 The core material refers to the non-encapsulated control group. Results showed that microencapsulation effectively protects the core sunscreen agent from UV damage, thus extending the effective protection time of the formulation on the skin under UV exposure.
[0101] Example 2: Preparation of nanocapsules under another implementation method
[0102] Weigh out 1 kg of each of the following ingredients in a mass ratio of 4:4:3:3: and mix them thoroughly to form the core material.
[0103] Following a core-to-wall material mass ratio of 1:1, 1 kg of N10 ethyl cellulose was measured and mixed evenly with the core material. Then, 100 g of sorbitan oleate (surfactant) and 150 g of PEG-40 hydrogenated castor oil (surfactant) were added. Subsequently, 2.5 L of ethyl acetate was added to fully wet the mixture, followed by 197.5 L of anhydrous ethanol to fully dissolve the homogeneous phase. The pH was then adjusted to 4.2 using anhydrous acetic acid to obtain phase A.
[0104] Weigh 1.8 kg of sodium lauryl sulfate, dissolve it in 200 L of pure water, and adjust the pH to 4.5 with anhydrous acetic acid to obtain phase B.
[0105] Using the rotor head of a homogenizer as the mixing center, phases A and B are injected into the mixing center at a flow rate ratio of 1:1 under the parameters of 40℃ and 2000rpm. After the two phases are mixed at high speed, the core material sunscreen agent and the wall material ethyl cellulose spontaneously complete the core-shell structure construction of the ethyl cellulose shell and the sunscreen agent core under the synergistic effect of hydrophobic effect, directional hydrogen bonding and steric hindrance repulsion, forming a milky white and bluish microcapsule suspension.
[0106] Microscopic examination of the microcapsules prepared in this embodiment under a polarizing microscope revealed that the ordered molecular self-assembly structure of the sunscreen core material inside the microcapsules brought about a significant Maltese cross extinction spot effect, indicating that the microcapsules prepared in this embodiment achieved supramolecular self-assembly.
[0107] Example 3: Preparation and Effect Demonstration of Nanocapsules under the Third Embodiment
[0108] Weigh out 1 kg of each of the following ingredients in a mass ratio of 3:3:4:5: mix them thoroughly, and use them as the core material.
[0109] Following a core-to-wall material mass ratio of 1:1, 1 kg of N10 ethyl cellulose was measured and mixed evenly with the core material. Then, 200 g of sorbitan oleate (surfactant) and 250 g of PEG-40 hydrogenated castor oil (surfactant) were added. Subsequently, 1.5 L of ethyl acetate was added to fully wet the mixture, followed by 73.5 L of anhydrous ethanol to fully dissolve the homogeneous phase. The pH was then adjusted to 4.8 using anhydrous acetic acid to obtain phase A.
[0110] Weigh 1.2 kg of sodium lauryl sulfate, dissolve it in 100 L of pure water, and adjust the pH to 4.2 with anhydrous acetic acid to obtain phase B.
[0111] Using an ultrasonic emulsification vessel as the mixing center, phases A and B were injected into the mixing center at a flow rate ratio of 3:4. Under ultrasonic parameters of 55℃, 40KHz, and 60W, the two phases were mixed at high speed. Under the synergistic effect of hydrophobic effect, directional hydrogen bonding, and steric hindrance repulsion, the core material sunscreen agent and the wall material ethyl cellulose spontaneously completed the core-shell structure construction of the ethyl cellulose shell and the sunscreen agent core, forming a milky white to bluish microcapsule suspension.
[0112] Microscopic examination of the microcapsules prepared in this embodiment under a polarizing microscope revealed that the ordered molecular self-assembly structure of the sunscreen core material inside the microcapsules brought about a significant Maltese cross extinction spot effect, indicating that the microcapsules prepared in this embodiment achieved supramolecular self-assembly.
[0113] Comparison Example
[0114] 1. Weigh out 1 kg of bis-ethylhexyloxyphenol methoxyphenyl triazine, butyl methoxydibenzoylmethane, ethylhexyl triazine ketone and diethylhexylbutamidotriazine ketone in a mass ratio of 4:4:3:4, and mix them evenly to form the core material.
[0115] Following a core-to-wall material mass ratio of 1:1, measure 1 kg of N10 ethyl cellulose and mix it evenly with the core material. Then, add 100 g of sorbitan oleate and 100 g of PEG-40 hydrogenated castor oil. After thoroughly wetting the mixture with 2 L of ethyl acetate, add 198 L of anhydrous ethanol to fully dissolve the homogeneous phase. Adjust the pH to 4.0 using anhydrous acetic acid to obtain phase A.
[0116] Weigh 1 kg of sodium lauryl sulfate, dissolve it in 200 L of pure water, and adjust the pH to 4.5 using anhydrous acetic acid to obtain phase B.
[0117] Using an ultrasonic emulsifying vessel as the mixing center, phases A and B were injected into the mixing center at a 1:1 flow ratio. The two phases were mixed at high speed (40 kHz, 60 W, 45 °C, instantaneous mixing and emulsification) to form a milky white, bluish, uniform microparticle suspension. Microscopic examination results are as follows... Figure 15 As shown, the results indicate that ethyl cellulose and the sunscreen agent failed to complete the expected spherical assembly of the core-shell structure, instead forming a large number of micron-sized short rods and irregular particles. In this control example, the surfactant ratio of the wall material to the alcohol phase was 1:0.2 by mass, indicating that the surfactant content in the alcohol phase was too low to achieve complete self-assembly.
[0118] 2. Weigh out 1 kg of bis-ethylhexyloxyphenol methoxyphenyl triazine, butyl methoxydibenzoylmethane, ethylhexyl triazine ketone and diethylhexylbutamidotriazine ketone in a mass ratio of 4:4:3.5:5, and mix them evenly to form the core material.
[0119] Following a core-to-wall material mass ratio of 1:1, measure 1 kg of N50 ethyl cellulose and mix it evenly with the core material. Then, add 200 g of sorbitan oleate and 200 g of PEG-40 hydrogenated castor oil. After thoroughly wetting the mixture with 2 L of ethyl acetate, add 98 L of anhydrous ethanol to fully dissolve the homogeneous phase. Adjust the pH to 8.0 using anhydrous acetic acid to obtain phase A.
[0120] Weigh 2 kg of sodium lauryl sulfate, dissolve it in 200 L of pure water, and adjust the pH to 8.0 using anhydrous acetic acid to obtain phase B.
[0121] Using the rotor head of a stator-rotor homogenizer as the mixing center, phases A and B were injected into the mixing center at a flow rate ratio of 1:2. The two phases were mixed at high speed (3000 rpm, 40℃, instantaneous mixing and emulsification) to form a milky white to bluish microcapsule suspension. Microscopic examination results are as follows. Figure 16 , 17 As shown, the results indicate insufficient self-assembly efficiency and the presence of numerous needle-like free core material crystals. After standing at room temperature for 48 hours, the free core material crystals grew and merged, producing a large amount of palpable granular precipitate, specifically as follows... Figure 18 As shown, this indicates that the pH of the system is too high, preventing self-assembly.
[0122] 3. Weigh out 1 kg of bis-ethylhexyloxyphenol methoxyphenyl triazine, butyl methoxydibenzoylmethane, ethylhexyl triazine ketone and diethylhexylbutamidotriazine ketone in a mass ratio of 4:4:3.5:5, and mix them evenly to form the core material.
[0123] Following a core-to-wall material mass ratio of 1:1, measure 1 kg of N20 ethyl cellulose and mix it evenly with the core material. Then, add 200 g of sorbitan oleate and 200 g of PEG-40 hydrogenated castor oil. After thoroughly wetting the mixture with 2 L of ethyl acetate, add 98 L of anhydrous ethanol to fully dissolve the homogeneous phase. Adjust the pH to 4.5 using anhydrous acetic acid to obtain phase A.
[0124] Weigh 0.2 kg of sodium lauryl sulfate, dissolve it in 100 L of pure water, and adjust the pH to 4.5 using anhydrous acetic acid to obtain phase B.
[0125] Using an ultrasonic emulsifying vessel as the mixing center, phases A and B were injected into the mixing center at a flow rate ratio of 2:1. The two phases were mixed at high speed (40 kHz, 60 W, 40 °C, instantaneous mixing and emulsification) to form a milky white to bluish emulsion suspension. After slight settling, some flocculent precipitation occurred. Figure 19 As shown. Microscopic examination results are as follows. Figure 20 As shown, the results indicate that a large number of irregularly shaped particles exist in the system, and these particles gradually aggregate and cross-link to form a gel-like precipitate as the storage time increases, failing to achieve ordered core-shell molecular self-assembly. This suggests that insufficient surfactant in the aqueous phase (below 0.3%) also prevents self-assembly.
[0126] 4. Weigh out 1 kg of bis-ethylhexyloxyphenol methoxyphenyl triazine, butyl methoxydibenzoylmethane, ethylhexyl triazine ketone and diethylhexylbutamidotriazine ketone in a mass ratio of 4:4:3.5:5, and mix them evenly to form the core material.
[0127] Following a core-to-wall material mass ratio of 1:1, measure 1 kg of N100 ethyl cellulose and mix it evenly with the core material. Then, add 1000 g of sorbitan oleate and 1000 g of PEG-40 hydrogenated castor oil. After thoroughly wetting the mixture with 2 L of ethyl acetate, add 98 L of anhydrous ethanol to fully dissolve the homogeneous phase. Adjust the pH to 4.5 using anhydrous acetic acid; this is phase A.
[0128] Weigh 1 kg of sodium lauryl sulfate, dissolve it in 100 L of pure water, and adjust the pH to 4.5 using anhydrous acetic acid. This is phase B.
[0129] Using the rotor head of a stator-rotor homogenizer as the mixing center, phases A and B were injected into the mixing center at a 1:1 flow ratio. The two phases were mixed at high speed (2500 rpm, 40°C, instantaneous emulsification) to form a milky white to bluish homogeneous microsuspension. Microscopic examination results are as follows. Figure 21 As shown, the results indicate that the solid phase of the microsuspension consists of tadpole-shaped or spindle-shaped particles, which does not match the expected spherical shell structure of the microcapsules. The surfactant ratio in the wall material to the alcohol phase is 1:2, indicating that even a high surfactant content in the alcohol phase cannot prevent complete self-assembly.
[0130] 5. Weigh out 1 kg of bis-ethylhexyloxyphenol methoxyphenyl triazine, butyl methoxydibenzoylmethane, ethylhexyl triazine ketone and diethylhexylbutamidotriazine ketone in a mass ratio of 4:4:3.5:5, and mix them evenly as the core material.
[0131] Following a core-to-wall material mass ratio of 1:0.2, measure 0.2 kg of N10 ethyl cellulose and mix it evenly with the core material. Then, add 200 g of sorbitan oleate and 200 g of PEG-40 hydrogenated castor oil. After thoroughly wetting the mixture with 2 L of ethyl acetate, add 98 L of anhydrous ethanol to fully dissolve the homogeneous phase. Adjust the pH to 4.5 using anhydrous acetic acid to obtain phase A.
[0132] Weigh 1 kg of sodium lauryl sulfate, dissolve it in 100 L of pure water, and adjust the pH to 4.5 using anhydrous acetic acid to obtain phase B.
[0133] Using an ultrasonic emulsifying vessel as the mixing center, phases A and B were injected into the mixing center at a 1:1 flow ratio. The two phases were mixed at high speed (40 kHz, 60 W, 50 °C, instantaneous mixing and emulsification) to form a milky white microsuspension. The microscopic examination results are as follows. Figure 22 As shown: The system contains numerous needle-like free core material crystals. For example... Figure 23 As shown, after standing at room temperature for 48 hours, the free core material crystallized, grew, and merged, with obvious precipitation and a large amount of granular precipitate. The core material:wall material ratio was 1:0.2, indicating that the amount of core material used was too high, making complete self-assembly impossible.
[0134] 6. Weigh out 1 kg of bis-ethylhexyloxyphenol methoxyphenyl triazine, butyl methoxydibenzoylmethane, ethylhexyl triazine ketone and diethylhexylbutamidotriazine ketone in a mass ratio of 4:4:3.5:5, and mix them evenly to form the core material.
[0135] Following a core-to-wall material mass ratio of 1:1, measure 1 kg of N10 ethyl cellulose and mix it evenly with the core material. Then, add 200 g of sorbitan oleate and 200 g of PEG-40 hydrogenated castor oil. After thoroughly wetting the mixture with 2 L of ethyl acetate, add 3 L of anhydrous ethanol to fully dissolve the homogeneous phase. Adjust the pH to 4.5 using anhydrous acetic acid to obtain phase A.
[0136] Weigh 1 kg of sodium lauryl sulfate, dissolve it in 100 L of pure water, and adjust the pH to 4.5 using anhydrous acetic acid to obtain phase B.
[0137] Using the rotor head of a homogenizer as the mixing center, phases A and B are injected into the mixing center at a flow rate ratio of 1:20. The two phases are mixed at high speed (3500 rpm, 45°C, instantaneous emulsification). During the mixing process, a large amount of fibrous white gel precipitates out and further entangles and aggregates into clumps during homogenization, such as... Figure 24 As shown. Microscopic examination results are as follows. Figure 25 As shown, the results indicate that almost no spherical microcapsules were present in the system, and the core and wall materials precipitated in long fibrous or irregular shapes, failing to achieve ordered core-shell molecular self-assembly. This suggests that insufficient solvent content prevents complete self-assembly.
[0138] 7. Weigh out 1 kg of bis-ethylhexyloxyphenol methoxyphenyl triazine, butyl methoxydibenzoylmethane, ethylhexyl triazine ketone and diethylhexylbutamidotriazine ketone in a mass ratio of 4:4:3.5:5, and mix them evenly to form the core material.
[0139] Following a core-to-wall material mass ratio of 1:1, 1 kg of N10 ethyl cellulose was measured and mixed thoroughly with the core material. Then, 200 g of sorbitan oleate and 200 g of PEG-40 hydrogenated castor oil were added. After thorough wetting with 2 L of ethyl acetate, 498 L of anhydrous ethanol was added to fully dissolve the homogeneous phase. The pH was adjusted to 4.5 using anhydrous acetic acid to obtain phase A.
[0140] Weigh 1 kg of sodium lauryl sulfate, dissolve it in 500 L of pure water, and adjust the pH to 4.5 using anhydrous acetic acid to obtain phase B.
[0141] Using an ultrasonic emulsifying vessel as the mixing center, phases A and B were injected into the mixing center at a 1:1 flow ratio. The two phases were mixed at high speed (40 kHz, 60 W, 50 °C, instantaneous mixing and emulsification) to form a milky white, semi-transparent microcapsule suspension, such as... Figure 26 As shown. Microscopic examination results are as follows. Figure 27 As shown, the results indicate that the amount of spherical microcapsules in the system is extremely small, and a large amount of irregularly shaped solid matter precipitates out. A large number of core and wall materials in the system failed to achieve ordered core-shell molecular self-assembly. This suggests that even excessive solvent usage cannot achieve complete self-assembly.
[0142] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Any modifications, alterations, substitutions, or variations made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention shall fall within the protection scope defined by the claims of the present invention.
Claims
1. A chemical sunscreen microcapsule, characterized in that: The chemical sunscreen microcapsules include nanocapsules, the nanocapsule components include wall material, solvent, surfactant and aqueous phase; the nanocapsules contain a core material, the core material being a chemical sunscreen agent; The wall material is ethyl cellulose; the solvent includes ethanol and ethyl acetate; the surfactant includes both lipophilic and hydrophilic surfactants; and the aqueous phase is an aqueous solution of acetic acid containing sodium lauryl sulfate.
2. The chemical sunscreen microcapsule according to claim 1, characterized in that: The viscosity grade of the ethyl cellulose is in the range of N3 to N200.
3. The chemical sunscreen microcapsule according to claim 1, characterized in that: The surfactant is a mixture of any two of the following: sorbitan oleate, PEG-40 hydrogenated castor oil, or sodium lauryl sulfate, and includes both lipophilic and hydrophilic surfactants.
4. The chemical sunscreen microcapsule according to claim 1, characterized in that: The content of sodium lauryl sulfate in the aqueous phase is 0.2–5.0%, w / w.
5. The chemical sunscreen microcapsule according to claim 1, characterized in that: The content of ethyl acetate in the solvent is ≤20%, v / v.
6. The chemical sunscreen microcapsules according to any one of claims 1 to 5, characterized in that: By mass ratio, wall material: core material = 20:1 to 1:3; by mass ratio, wall material: solvent = 1:8 to 1:400; by mass ratio, wall material: surfactant in alcohol phase = 1:0.25 to 1:1.6; based on solvent volume, aqueous phase: solvent = 1:4 to 100:1, v / v.
7. A method for preparing the chemical sunscreen microcapsules according to any one of claims 1 to 6, characterized in that: The preparation method includes the following steps: (1) Preparation of phase A: Weigh the wall material and core material, add the surfactant, then add solvent, dissolve fully until homogeneous, and adjust the pH to 3.0-5.5 using acetic acid; (2) Prepare phase B: Prepare an aqueous solution of acetic acid containing sodium lauryl sulfate, and adjust the pH to 3.0-5.5 using acetic acid; (3) Mix phase A and phase B at a flow rate of 7:3 to 1:20 in a stator-rotor homogenizer or ultrasonic emulsifier to achieve self-assembly and encapsulation of the supramolecular nanocapsules.
8. The preparation method according to claim 7, characterized in that: The preparation method further includes: (4) Wall solidification: The nanocapsules prepared in step (3) are chemically cross-linked with glutaraldehyde to obtain solidified microcapsules.
9. The preparation method according to claim 8, characterized in that: The preparation method further includes: (5) Separate the solidified microcapsules from the system.
10. The application of the preparation method according to any one of claims 7 to 9 in the preparation of sunscreen cosmetics.
